Implementation of Religious Programs And Their Impact on Students' Spiritual Intelligence - Pulungan, Nur Muhibbah; Anhar, Anhar; Asfiati, Asfiati (Fahmina: Jurnal Pendidikan Islam, 2023)
Student High School (SMA) 3 Panyabungan programs various religious activities that have an impact on students' spiritual intelligence. Based on the initial findings, this study conducted an in-depth study of the implementation of religious programs and their impact on improving students' spiritual intelligence. The formulation of the research problem is how is the implementation of the students' religious program at SMA Negeri 3 Panyabungan? and how does the implementation of the religious program affect the spiritual intelligence of students in SMA Negeri 3 Panyabungan? The data collection method used was direct observation and interviews with school principals, religious program guidance teachers, Islamic religious education teachers and students of SMA Negeri 3 Panyabungan, and supported by documentation data relevant to the problem described. Next, the research was analyzed using the qualitative descriptive analysis method of the Miles and Huberman model consisting of data reduction, data presentation and conclusion. The results showed that the implementation of religious programs seemed to follow the flow of the GPDCA Cycle, namely Goal, Plan, Do, Check and Act. The four stages are carried out in an integrated manner. The impact of the implementation of religious programs on students' spiritual intelligence includes students having an Islamic vision of life, students having broader and deeper religious knowledge, having stronger faith and piety, behaving honestly, responsibly, disciplined, having high self-confidence, and religious creativity.